PENGARUH PERHATIAN ORANG TUA, KEDISIPLINAN, DAN MINAT BELAJAR SISWA TERHADAP PRESTASI BELAJAR - Inna Ra’ufuatun (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2015)
In this issue we researchers studying include: 1. No significant relationship between parents' attention towards learning achievement of economic subjects in class XI student of SMAN 5 Balikpapan? 2. Is there a significant influence between the discipline of learning achievement of economic subjects in class XI student of SMAN 5 Balikpapan? 3. Are there significant relationship between student interest towards learning achievement of economic subjects in class XI student of SMAN 5 Balikpapan? 4. Is there a significant influence jointly or simultaneously between the parents' attention, discipline, and student interest towards learning achievement of economic subjects in class XI student of SMAN 5 Balikpapan? Number of students 107 students by taking a sample of 83 students. Based on hypothesis testing 1. The coefficient Fhitung 2795> compared with a value of 2.710 Ftabel so Ho rejected, meaning that 31.0% of the change is determined achievement of parental supervision. Hypothesis 2. The coefficient Fhitung 2728> of Ftable value of 2.710, then Ho is rejected, meaning that 40.0% of the change is determined discipline feat. Hypothesis 3. The coefficient Fhitung 2898> of Ftable value of 2.710, then Ho is rejected, meaning that the changes are determined interest in student learning achievement. The effective contribution of parental supervision, discipline and student interest in learning together had a positive impact on student achievement amounted to 92.1%, the effective contribution of 31.0% of parental attention, discipline 40.0%, and interest in learning students 21.1% while 7.9% of other factors.